Evaluation Performance of Social Organization in Setu District – South Tangerang - Rahmi Andini Syamsuddin; Lisdawati; Agung Tri Putranto (Jurnal Ekonomi dan Bisnis Jagaditha, 2020)
This study aims to measure the performance of Posyantek as a social organization in community empowerment in Setu District, South Tangerang. This study was designed in a qualitative descriptive type using data collection methods through interviews, observation, and documentation. Researchers will use indicators including productivity, service quality, responsiveness, responsibility, accountability in measuring the performance of Posyantek. The results obtained that there are still low-performance indicators, i.e. responsibility and accountability indicators. There is always a lack of communication between Posyantek and the surrounding community, which causes some Posyantek programs that are not running well. The insufficient number of Posyantek employees who are proficient in IT also causes the TTG program to be less than optimal. The absence of a standard organizational structure so that the flow of activities, especially TTG, is still not targeted.